2021
DOI: 10.1093/nar/gkab445
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent recruitment of SRSF1 and SRSF7 to intronless lncRNA NKILA promotes nuclear export via the TREX/TAP pathway

Abstract: The TREX-TAP pathway is vital for mRNA export. For spliced mRNA, the TREX complex is recruited during splicing; however, for intronless mRNA, recruitment is sequence dependent. However, the export of cytoplasmic long noncoding RNA (lncRNA) is poorly characterized. We report the identification of a cytoplasmic accumulation region (CAR-N) in the intronless lncRNA, NKILA. CAR-N removal led to strong nuclear retention of NKILA, and CAR-N insertion promoted the export of cDNA transcripts. In vitro RNP purification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 58 publications
(80 reference statements)
4
13
0
Order By: Relevance
“…RBM4 , which is the most enriched RBP in the cytosolic genes, contains a C-terminal alanine-rich domain that potentially mediate RNA export ( Lai et al 2003 ). RNA export function of SRSF1 , another top enriched RBP, is also supported by a few published literatures ( Das and Krainer 2014 ; Khan et al 2021 ). However, the functional roles of RBP in RNA localization, such as RNA export, were still very limited.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…RBM4 , which is the most enriched RBP in the cytosolic genes, contains a C-terminal alanine-rich domain that potentially mediate RNA export ( Lai et al 2003 ). RNA export function of SRSF1 , another top enriched RBP, is also supported by a few published literatures ( Das and Krainer 2014 ; Khan et al 2021 ). However, the functional roles of RBP in RNA localization, such as RNA export, were still very limited.…”
Section: Resultssupporting
confidence: 57%
“…For separation of nuclear and cytoplasmic fractions, the extraction kit (Beyotime China, P0027) was used and followed the same procedures as previous study ( Khan et al 2021 ). Total RNA was used as input material for the RNA sample preparations.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study indicated that cytoplasmic accumulation region (CAR-N) removal in NKLA, an intron-less lncRNA, results in significant nuclear restriction and insertion of CAR-N increased cDNA transcript export. Researchers also found that TREX-TAP pathway depletion strongly restricts NKILA to the nucleus and that removal of CAR-N does not prevent breast cancer cell migration [ 28 ]. Previously, Zuckerman et al depleted several proteins that are involved in nuclear export.…”
Section: Long Non-coding Rna Molecular Mechanisms and Cancer Involvementmentioning
confidence: 99%
“…A recent study indicated that cytoplasmic accumulation region (CAR-N) removal in NKLA, an intronless lncRNA, results in significant nuclear restriction and insertion of CAR-N increased cDNA transcript export. Researchers also found that TREX-TAP pathway depletion strongly restricts NKILA to the nucleus and that removal of CAR-N does not prevent breast cancer cell migration [26]. Previously, Zuckerman et al depleted several proteins involved in nuclear export.…”
Section: Lncrna Nuclear Accumulation Splicing and Gene Regulationmentioning
confidence: 99%